Possibilities of High Resolution Inductively Coupled Plasma Optical Emission Spectrometry in the Determination of Trace Elements in Environmental Materials - Nikolaya Velitchkova; Olga Veleva; Serafim Velichkov; Nonka Daskalova (Journal of Spectroscopy)
This paper presents new quantitative data for the spectral interferences obtained by high resolution 40.68 MHz radial viewing inductively coupled plasma optical emission spectrometry (HR-ICP-OES) in the determination of Zn, Cd, Sb, Cu, Mn, Pb, Sn, Cr, U, and Ba in environmental materials in the presence of a complex matrix, containing Al, Ca, Fe, Mg, and Ti. The -concept for quantification of spectral interferences was used. The optimum line selection for trace analysis of a variety of multicomponent matrices requires the choice of prominent lines, which are free or negligibly influenced by line interference problems. The versatility of -concept as basic methodology was experimentally demonstrated in the determination of trace of elements in soil and drinking water. The detection limits are lower in comparison with corresponding threshold concentration levels for soil and drinking water in accordance with environmental regulations. This paper shows the possibilities of present day ICP-OES equipment in the direct determination of trace elements (without preconcentration of impurities) in environmental samples.